Pharmacokinetics and Optimal Dosing of Levofloxacin in Children for Drug-Resistant Tuberculosis: An Individual Patient Data Meta-Analysis - White, Yasmine N; Solans, Belen P; Denti, Paolo; van der Laan, Louvina E; Schaaf, H Simon; Vonasek, Bryan; Malik, Amyn A; Draper, Heather R; Hussain, Hamidah; Hesseling, Anneke C; Garcia-Prats, Anthony J; Savic, Radojka M (Clinical infectious diseases, 2024)
Abstract Background Each year 25 000–32 000 children develop rifampicin- or multidrug-resistant tuberculosis (RR/MDR-TB), and many more require preventive treatment. Levofloxacin is a key component of RR/MDR-TB treatment and prevention, but the existing pharmacokinetic data in children have not yet been comprehensively summarized. We aimed to characterize levofloxacin pharmacokinetics through an individual patient data meta-analysis of available studies and to determine optimal dosing in children. Methods Levofloxacin concentration and demographic data were pooled from 5 studies and analyzed using nonlinear mixed effects modeling. Simulations were performed using current World Health Organization (WHO)–recommended and model-informed optimized doses. Optimal levofloxacin doses were identified to target median adult area under the time-concentration curve (AUC)24 of 101 mg·h/L given current standard adult doses. Results Data from 242 children (2.8 years [0.2–16.8] was used). Apparent clearance was 3.16 L/h for a 13-kg child. Age affected clearance, reaching 50% maturation at birth and 90% maturation at 8 months. Nondispersible tablets had 29% lower apparent oral bioavailability compared to dispersible tablets. Median exposures at current WHO-recommended doses were below the AUC target for children weighing <24 kg and under <10 years, resulting in approximately half of the exposure in adults. Model-informed doses of 16–33 mg/kg for dispersible tablets or 16–50 mg/kg for nondispersible tablets were required to meet the AUC target without significantly exceeding the median adult Cmax. Conclusions Revised weight-band dosing guidelines with doses of >20 mg/kg are required to ensure adequate exposure. Further studies are needed to determine safety and tolerability of these higher doses. Most children receiving levofloxacin for the treatment or prevention of rifampicin- and multidrug-resistant tuberculosis at currently recommended doses will not achieve adult-matched exposures. New guidelines with increased levofloxacin doses for children weighing <24 kg are proposed to ensure adequate exposure.